Estudo de arranjos de antenas de microfita com Patch quase-fractal para comunicações sem fio - Andrade, Betoven Oliveira de (2014)
In this dissertation, are presented two microstrip antennas and two arrays for applications in wireless communication systems multiband. Initially, we studied an antenna and a linear array consisting of two elements identical to the patch antenna isolated. The shape of the patch used in both structures is based on fractal geometry and has multiband behavior. Next a new antenna is analyzed and a new array such as initial structure, but with the truncated ground plane, in order to obtain better bandwidths and return loss. For feeding the structures, we used microstrip transmission line. In the design of planar structures, was used HFSS software for the simulation. Next were built and measures electromagnetic parameters such as input impedance and return loss, using vector network analyzer in the telecommunications laboratory of Federal University of Rio Grande do Norte. The experimental results were compared with the simulated and showed improved return loss for the first array and also appeared a fourth band and increased directivity compared with the isolated antenna. The first two benefits are not commonly found in the literature. For structures with a truncated ground planes, the technique improved impedance matching, bandwidth and return loss when compared to the initial structure with filled ground planes. Moreover, these structures exhibited a better distribution of frequency, facilitating the adjustment of frequencies. Thus, it is expected that the planar structures presented in this study, particularly arrays may be suitable for specific applications in wireless communication systems when frequency multiband and wideband transmission signals are required.